Reliability centered maintenance methodology for product in design improvement phase : a case study on dough presser - Nurulhuda Abu Bakar (School of Manufacturing Engineering, Universiti Malaysia Perlis, 2017)
The main goal of this research is to propose the RCM methodology specifically for the equipment in design improvement phase and validate through the objectives which consist of ; to study the effect of the root cause analysis tool replacement from FMEA (Failure Mode and Effect Analysis) to Fault Tree Analysis (FTA) ; to examine the difference in FMEA result with respect to the data sources (block diagram versus FTA) ; to investigate the benefit of the integration between Risk Priority Number (RPN) and the criticality analysis.